(untitled) (BIBECHANA, 2010)
We have determined the equilibrium constants and pairwise interaction energies between the species and the complexes of liquid CuSn, AgAl and FeSi, alloys on the basis of regular associated solution model. These parameters are then used to estimate the heat of mixing of each alloy. The observed asymmetry in the heat of mixing of each alloy with respect to concentration is well explained. Key Words: Free energy of mixing; Asymmetry; Binary alloys, interaction energy The corrected version of this PDF was loaded on 8/12/2010. DOI: 10.3126/bibechana.v6i0.3931 BIBECHANA Vol. 6, March 2010 pp.1-8